A case study on effect of the magnetic storm of 20 November 2003 on GPS ionospheric scintillation at Vanimo station. Issue 9 (1st November 2015) - Yang, Shenggao; Fang, HanXian; Weng, Libin; Luo, Jie; Zhou, Xiaoke
Abstract The magnetic storm of November 20–21, 2003 was a super storm with minimum Dst −438 nT. Using the GPS ionospheric scintillation data recorded at Vanimo station near the magnetic equator, we investigate the behaviors of the ionospheric scintillations during the storm. The amplitude ionospheric scintillations were enhanced evidently at 19:00–20:00 LT on November 20 2003, corresponding to the sudden increased solar wind speed, steep increase and reorientation in IMF components, intensification of AE and decreased Dst (Sym-H). Severe density depletion region over Vanimo station, and density enhanced areas adjacent to its northern and southern directions were observed simultaneously. It is the prompt penetration of eastward electric field associated with the southward turning of the IMF and intensification of AE that elevate the ionospheric plasma to certain height through the E × B mechanism, then the plasma drifts along the magnetic lines to low latitude, thus forming the great north–south gradient of electron density. Therefore, the sudden change of the electron density during the period may be responsible for the storm-induced scintillation enhancements at Vanimo station.